Second-Look Endoscopy in Hospitalized Severe Ulcerative Colitis: A Retrospective Cohort Study - Borren, Nienke Z (Inflamm Bowel Dis, 2019)
BACKGROUND: Acute severe ulcerative colitis (ASUC) is a serious complication of ulcerative colitis (UC). Management of partial responders to steroids or rescue therapy remains challenging. Whether there is a role for re-look sigmoidoscopic evaluation in disease management is unknown. METHODS: Our study cohort consisted of patients who underwent 2 sigmoidoscopic procedures during the same index hospitalization for ASUC at our center. Reasons for repeat endoscopic evaluation and endoscopic and histologic severity of inflammation during both procedures were noted. Multivariable regression models were performed to identify predictors of improvement at the second endoscopic assessment and to determine the independent effect of such an improvement on in-hospital colectomy and at 3, 6, and 12 months. RESULTS: Our study included 49 patients (mean age, 42 years; 52% women). Just under one-third of patients (30%) were noted to have improved endoscopic appearance at the second sigmoidoscopy, at a median of 9 days after initial exam. None of the patients who had improvement on the second endoscopy underwent in-hospital colectomy, compared with 46% of those with worsening or persistent disease (P = 0.002). Similar differences in the improved group persisted at 3 months (P = 0.007) and 6 months (P = 0.027). Histologic severity at the first endoscopy was associated with increased risk of colectomy in-hospital (odds ratio, 3.8; 95% confidence interval, 1.02–14.21) and at 3 and 6 months. CONCLUSIONS: After a median interval of 9 days, endoscopic improvement was noted in 30% of patients with ASUC undergoing a second sigmoidoscopy, which predicted lower rates of colectomy in-hospital and at 3 and 6 months.